Opuntia ficus indica: un coagulante alternativo para el tratamiento de aguas con alta turbidez y pH ácido / Opuntia ficus indica: an alternative coagulante for the treatment of waters with high turbidity and acid pH - Caldera, Yaxcelys; Millán, Emmanuel; González, Yoalis; Gutiérrez, Edixón (Impacto Científico, 2020)
RESUMENEl pH del agua tiene efectos durante el tratamiento de las aguas por coagulación, puesto que afecta el tiempo para la formación de flóculos, la carga sobre las partículas coloidales y las dosis requeridas, existiendo un intervalo óptimo para cada coagulante. El objetivo de esta investigación es evaluar la efectividad del coagulante Opuntia ficus indica durante el tratamiento de aguas turbias con pH ácido. Se utilizó agua sintética avalores de turbidez de 100, 150 y 200 UNT y pH de 5 unidades. El coagulante O. ficus indica se desecó en una estufa a una temperatura menor a 60 ºC y se preparó una mezcla al 10 % m/v, de la cual se evaluaron las dosis de 50, 100, 150, 200 y 250 mg/L. Se determinaron los parámetros pH, color y turbidez antes y después de la clarificación (coagulación, floculación, sedimentación y filtración). Los resultados demostraron que el coagulante O. ficus indica desecado es eficiente para remover turbidez (63,13 % -96,39 %) y color (71,5 % - 93,5 %) de aguas con alta turbidez inicial (100, 150 y 200 UNT) en condiciones de pH ácido (5 unidades). Las dosis óptimas del coagulante fueron 50 y 100 mg/L. Se observó que el pH ácido de las aguas no afectó significativamente la eficiencia del coagulante. Opuntia ficus indica representa un coagulante alternativo para tratar aguas turbias con pH ácido.ABSTRACTThe pH of the water has effects during the treatment of the waters by coagulation,since it affects the time for the formation of flocs, the load on colloid particles and the required doses, existing an optimal interval for each coagulant. The objective of this research is to evaluate the efficiency of coagulant Opuntia ficus indica during treatment the water turbid with acid pH. Synthetic water with turbidity values of 100, 150 and 200 NTU and pH 5 units, was used. The coagulant O. ficus indica was dried in an oven at a temperature lower than 60 ºC and a mixture at 10% m/v was prepared, rom which the doses of 50, 100, 150, 200 and 250 mg/L were evaluated. The parameters pH, color and turbidity were determined before and after of the clarification (coagulation, flocculation, sedimentation and filtration). The results showed that the coagulant O. ficus indica dried is efficient to remove turbidity (63.13 % - 96.39 %) and color (71.5% - 93.5 %) of waters with high initial turbidity (100, 150 and 200 NTU) under acid pH conditions (5 units). The optimal doses of the coagulants were 50 and 100 mg/L. It was observed that the acid pH of the waters did not significantly affect the efficiency of the coagulant. Opuntia ficus indica represents an alternative coagulant to treat turbid waters with acidic pH.